Conversion and regionalization of spatial soil information to estimate ecological habitat classes - Laborczi, Annamári; Bakacsi, Zsófia; Szabó, József; Pásztor, László (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
Demands on soil information rarely can be fulfilled directly by available data. In our present work the available soil information have been harmonized with required data to ecological-related research. The harmonization could not be achieved directly, therefore some conversions had to be made to get the proper information to more than 3000 spots. The first step was to elaborate the method of matching between the Digital Kreybig Soil Information System (DKSIS) and the required categories. The practical implementation according to this model was on the one hand spatial query for polygon data of DKSIS. On the other hand we derived maps by indicator kriging from soil profile data, and the spatial query has been executed to these maps. More than 3000 spots have been classified into the most probable categories (saline, sand, loess, peaty, forest, alluvial) according to the maximum proportion of the calculated area values. The newly elaborated results will be a basis of further nationwide ecological researches.
Keywords: soil; spatial soil information; data harmonization